2017
DOI: 10.5513/jcea01/18.2.1917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tytanit� on the yield and yield components of very early-maturing potato cultivars

Abstract: The growing period for early potatoes is extremely short, only 50-80 days from planting to harvest. To obtain a high marketable tuber yield in such a short period good conditions for plant growth must be ensured. In modern agriculture, plant growth stimulants have been gaining increasing importance. Although titanium (Ti) is neither a major nor minor nutrient for plants, it is classified as a beneficial element for plant growth. This paper analyses the effect of dose (0.2 dm ) on the yield and yield components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These results are consistent with the research of Gugała et al (2017) who obtained the highest total rise in yield of potato tubers applying the Sencor 70 WG herbicide just before sprouting and then the Asahi SL biostimulator twice. A beneficial effect of the application of biostimulators on yielding of cultivated plants was also recorded by Matysiak et al (2011), Kalinowski and Wadas (2017). Mikos-Bielak and Czeczko (2002), assessing the effective application of Atonik biostimulator in the cultivation of medium late potato Ania, demonstrated that single application of 0.1% solution of this preparation on leaves before flowering increased the total yield by around 14%.…”
Section: Resultssupporting
confidence: 52%
“…These results are consistent with the research of Gugała et al (2017) who obtained the highest total rise in yield of potato tubers applying the Sencor 70 WG herbicide just before sprouting and then the Asahi SL biostimulator twice. A beneficial effect of the application of biostimulators on yielding of cultivated plants was also recorded by Matysiak et al (2011), Kalinowski and Wadas (2017). Mikos-Bielak and Czeczko (2002), assessing the effective application of Atonik biostimulator in the cultivation of medium late potato Ania, demonstrated that single application of 0.1% solution of this preparation on leaves before flowering increased the total yield by around 14%.…”
Section: Resultssupporting
confidence: 52%
“…Tuber weight. Tytanit ® had a significant effect on the tuber weight per plant described in the work by Kalinowski and Wadas [2017]. In the three years of the study, the tuber weight per plant was higher by 48 g (8%), on average, compared to the control object without this plant growth stimulant (tab.…”
Section: Plant Height and Above-ground Plant Biomassmentioning
confidence: 82%
“…Some comparative studies have shown that higher-yielding potato cultivars have a lower content of mineral elements in tubers than lower-yielding cultivars grown in the same conditions (White et al, 2009), which was not confirmed in the discussed study in the early date of potato harvest. The tuber yield of 'Lord' and 'Miłek' cultivars harvested 75 days after planting did not differ significantly (Kalinowski and Wadas, 2017). Regardless of the experimental factors, the tubers contained the most nitrogen, phosphorus, potassium and calcium and, at the same time, the least magnesium and sulphur in the cool and very moist growing season of 2009.…”
Section: Roots Most Macroelements Are Taken Up By a Combination Of Tmentioning
confidence: 86%
“…According to Sawicka and Mikos-Bielak (1995), an increase in potato tuber yield may be associated with a decrease in levels of certain, but not all, minerals in tubers. Tytanit ® as a growth stimulant caused an increase in the plant height and aboveground plant biomass and tuber weight per plant (Wadas and Kalinowski, 2017a), and as the result an increase in the yield of new potatoes of 'Lord' and 'Miłek' cultivars (Kalinowski and Wadas, 2017), but did not affect the macroelement contents in tubers, except for sodium. Leaf-absorbed titanium is translocated to roots via phloem and accumulated in the chloroplasts (Kelemen et al, 1993;Lyu et al, 2017).…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 95%